Spondylitis Presenting With Cauda Equina Syndrome in a 12 Year Old Boy (Journal of Dhaka Medical College, 2020)
A 12-year-old boy presented with a 2-week history of low back pain and 10-day history of weakness of the lower limbs,5-day history of inability to pass urine. An MRI scan of the lumbar spine showed dehiscent lamina of L5,S1 and an epidural abscess. He was admitted to hospital and treated with a high dose of IV antibiotics followed by radical surgical excision of the lesion. Histopathology showed features of abscess. He eventually recovered bowel and bladder control and regained muscle power in the lower limbs. Infection is not a common cause of cauda equina syndrome. Aggressive surgical treatment combined with a prolonged antibiotic regime is recommended to achieve a satisfactory result.J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 119-122